Investigating the emigration intention of health care workers: A cross‐sectional study - Badru, Oluwaseun Abdulganiyu; Alabi, Tunde Adeyemo; Okerinde, Samuel Sijibomi; Kabir, Muhammad Auwal; Abdulrazaq, Aisha; Adeagbo, Oluwafemi Atanda; Badru, Fatai Adesina (Nursing open, 2024)
Aims To (1) explore the intramigration experience of HCWs within Nigeria, (2) explore the migration intention of health care workers (HCWs) in Nigeria and (3) identify the predictors of migration intention among HCWs in Nigeria. Design Cross‐sectional study. Methods The online survey was used to collect data from 513 HCWs in Nigeria between May and June 2023. Crude and adjusted logistic regression were used to identify factors associated with emigration intention. Analyses were performed on SPSS version 26 at a 95% confidence interval. Results The study found that 34.4% had intramigration experience, and the rate of intention to emigrate to work in another country was 80.1%. The United Kingdom was the most preferred destination (109 HCWs), followed by Canada (92 HCWs) and the United States (82 HCWs). At the multivariate level, emigration intention was associated with the experience of burnout and duration of practice as a HCW. Nurses had higher emigration intentions than medical doctors. Conclusions Many HCWs in Nigeria appear to have emigration intent, and nurses are more likely to be willing to migrate than doctors. The Nigerian government may want to explore strategies to reverse the emigration intent of the HCWs in Nigeria.